Misreporting of Energy Intake From Food Records Completed by Adolescents: Associations With Sex, Body Image, Nutrient, and Food Group Intake - Jones, Louise; Ness, Andy; Emmett, Pauline (Frontiers in Nutrition, 2021)
Background and Objectives: A healthy diet during adolescence is important for growth and pubertal development. Assessing the diet of adolescents may be challenging as the behavioural factors and food habits which impact on what they eat may also affect how they report dietary intake. This study assesses factors associated with the misreporting of dietary intake. Methods: Adolescents (n = 4,844; average age 13.8 years) from the Avon Longitudinal Study of Parents and Children (ALSPAC) completed a 3-day diet record. Misreporting was estimated using an individualised method, and adolescents were categorised by reporting status. Foods were categorised as core and noncore foods to evaluate diet quality. Body composition measurements were recorded at a research clinic. Information on dieting, weight concern, family socioeconomic status, and parental BMI were collected via questionnaires. Binary logistic regression was performed, in boys and girls separately, to investigate factors associated with underreporting of dietary intake. Results: Girls were much more likely than boys to be dissatisfied with their weight and to diet, but showed similar levels of underreporting ( 67%). In adjusted regression analysis underreporters (UR) were more likely to be overweight or obese: OR in boys 2.8 (95% CI 1.7–4.8) and in girls 2.2 (95% CI 1.5–3.2). Dissatisfaction with weight and dieting were positively associated, and perception of being underweight negatively associated with underreporting in boys. Perception of being overweight, dieting, and exact age were positively associated with underreporting in girls. UR obtained a greater percentage of energy from protein and a smaller percentage of energy from fat; they reported greater intake of core foods and lower intakes of non-core foods than plausible reporters. Conclusion: A large proportion of adolescents underreported their dietary energy intake. This was associated with their body weight status and body image and had a differential effect on their estimated food and macronutrient intakes. Assessment of misreporting status is essential when collecting and interpreting dietary information from adolescents.